Effect of lattice strain on the polychromatic emission in ZnO nanostructures for white light emitting diode application. (August 2018) - Biju, C.S.; Suresh, S.; Sahaya Jude Dhas, S.; Gowri Shankar Rao, R.
Abstract: In this work, we report that flower shaped architecture of ZnO assembled by individual nanopetals of an average thickness ∼93 nm has been achieved by selective self – etching method. The presence of oxygen deficiency is confirmed by EDX and ATR measurements. ZnO nanopetals prepared at 80 °C exhibit enhanced polychromatic defect emissions of blue, green and red (BGR) as compared to samples annealed at higher temperatures. The improved luminescence emission of BGR is attributed to the higher lattice strain and dislocation density induced in ZnO due to native defects. As the annealing temperature is reduced, the dislocation density increases from 7.60 × 10 13 to 3.99 × 10 15 lines/m 2, whilst, lattice strain increases from 0.0079 × 10 −3 to 1.81 × 10 −3 . The observed high luminescence emission is due to flower shaped architecture making it suitable for the fabrication of solid-state white light emitting diodes. Graphical abstract: Image 1 Highlights: Preparation of flower shaped ZnO assembled by nanopetals using selective self-etching method. Confirmation of oxygen deficiency by EDX and ATR methods. Lattice strain and dislocation density reduce with annealing temperature. ZnO nanostructure dried at 80 °C exhibits enhanced polychromatic emission pertaining to Blue, Green and Red.